Методы исключения неизвестных из систем линейных неравенств и их приложения - Остапенко, В.В.; Финин, Г.С. (Український математичний журнал, 2001)
Вивчаються методи вилучення одного невідомого або групи невідомих із системи лінійних нерівностей. Обгрунтування цих методів проводиться на основі теореми Хеллі. Методи застосовуються для обчислення течій у мережах із узагальненим принципом збереження. We study methods for the elimination of an unknown or a group of unknowns from systems of linear inequalities. We justify these methods by using the Helly theorem. The methods considered are applied to the calculation of streams in networks with a generalized conservation law.